Comparison between on-demand use of sertraline and dapoxetine for treating patients with premature ejaculation. Issue 4 (December 2016) - Mahran, Ali; Morsy, Hanan
Abstract : Objective: Premature ejaculation (PE) is one of the most common sexual dysfunctions among men. This study was carried out to assess the quality of life and the on-demand effect of two selective serotonin reuptake inhibitors (dapoxetine and sertraline) on vaginal latency and coital frequency in a sample of Egyptian men complaining of PE. Patients and methods: In the current study we included 64 men attending Andrology Outpatient Clinic, Assiut University Hospitals, Egypt. These participants were evaluated using the Arabic Index of PE questionnaire, measuring the intravaginal ejaculation latency time (IELT) time and coital frequency before and after therapy. Results: The mean age was 34.81±7.19 years in the dapoxetine group and 37.47±7.22 years in the sertraline group. The mean IELT in the dapoxetine group was 0.71±0.16 min before therapy, and it increased significantly to 2.51±0.11 min after therapy ( P =0.001). The mean IELT for the sertraline group before therapy was 0.65±0.15 min, and it increased significantly to 2.61±0.11 min ( P =0.001). Significant correlations were found between Arabic Index Premature Ejaculation (AIPE) scores and coital frequency before and after treatment in both groups. Conclusion: Patients with severe PE showed mild-to-moderate improvement in IELT and AIPE. Both groups showed improvement in IELT and AIPE scores. The sertraline group was better compared with the dapoxetine group as regards ejaculation latency, ejaculation control, and patient satisfaction.